New meanings of “home” in South Africa - Marchetti-Mercer, Maria (University of the Free State, 2006)
The search for a place we can call “home” and where we feel we can truly belong is a common human experience. This article explores the different meanings attached to the concept of home and how these influence our experience of belonging. These will be discussed in the context of individual as well as family and cultural experiences, with special emphasis on the contributions of family therapy towards this understanding. The article will also explore how finding a “home” is particularly relevant in present-day post-apartheid South African society. In conclusion it will be argued that “home” may be a fluid concept which requires mobility and flexibility in order to accommodate the complexities of a postmodern world.

Die soektog na ’n “tuiste” waar ons werklik geborge kan voel, is ’n algemeen menslike versugting. In hierdie artikel ondersoek die outeur die verskillende betekenisse wat die term “tuiste” inhou en hoe dit ons ervaring van om iewers tuis te hoort, raak. Hierdie aspekte word bespreek in die konteks van individuele sowel as gesinsverband en kulturele ervarings, met besondere klem op die bydrae wat gesinsterapie lewer tot ’n beter insig daarvan. Die besondere relevansie van die soeke om ’n “tuiste” in die postapartheid Suid-Afrikaanse samelewing te vind, word ook in die artikel onder die loep geneem. Ten slotte word gefokus op die moontlikheid dat die behoefte aan ’n “tuiste” ’n vloeibare konstruk is, wat die beweeglikheid en buigsaamheid van ’n komplekse postmoderne wêreld in ag moet neem.
Keywords: Home; Experience of belonging; Family; "Home” in a postmodern world